2017
DOI: 10.5489/cuaj.4303
|View full text |Cite
|
Sign up to set email alerts
|

Maximal testosterone suppression in the management of recurrent and metastatic prostate cancer

Abstract: Introduction: Testosterone suppression, or androgen-deprivation therapy (ADT), is an established treatment for recurrent and metastatic prostate cancer (PCa). Based on the accuracy and sensitivity of early assays (c. 1960-1970), the castrate testosterone level was set at ≤1.7 nmol/l. Improved sensitivity of testosterone assays shows that both surgical and medical castration can achieve levels <0.7 nmol/l. However, the clinical implications and importance of maximum testosterone suppression remains a subject of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 37 publications
(84 reference statements)
0
33
0
2
Order By: Relevance
“…To date, no studies have evaluated if ADT in PCa patients associates with the progression of frailty syndrome over time, taking into account that ADT in PCa greatly reduce the levels of circulating testosterone sometimes achieving undetectable levels, in order to limit cancer relapses and disease progression [18][19][20] and could accelerate the progression of frailty syndrome. There is a consistent body of evidence that relate testosterone deficiency to systemic inflammatory responses e.g., both animal studies and human studies showed that testosterone deficiency is associated with an increase in pro-inflammatory cytokines and testosterone substitution reduced pro-inflammatory cytokines in patients with coronary artery disease, prostate cancer and diabetes mellitus through the decrease in pro-inflammatory cytokines (IL-1β, IL-6, and TNF-alpha) [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…To date, no studies have evaluated if ADT in PCa patients associates with the progression of frailty syndrome over time, taking into account that ADT in PCa greatly reduce the levels of circulating testosterone sometimes achieving undetectable levels, in order to limit cancer relapses and disease progression [18][19][20] and could accelerate the progression of frailty syndrome. There is a consistent body of evidence that relate testosterone deficiency to systemic inflammatory responses e.g., both animal studies and human studies showed that testosterone deficiency is associated with an increase in pro-inflammatory cytokines and testosterone substitution reduced pro-inflammatory cytokines in patients with coronary artery disease, prostate cancer and diabetes mellitus through the decrease in pro-inflammatory cytokines (IL-1β, IL-6, and TNF-alpha) [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are relevant to previous studies that have demonstrated that testosterone levels <0.7 nM correlate with a longer time to CRPC progression (4, 5). Patients with nadir testosterone levels during the first year of ADT ≤0.7 nM had a longer time to CRPC compared to those with levels either between 0.7 and 1.7 nM or >1.7 nM (10.0 vs 7.21 vs 3.62 years respectively; P = 0.015) (14, 24). In addition, testosterone breakthroughs above 1.1 and 1.7 nM have been found to be predictors of progression to CRPC when compared to patients without breakthrough (88 vs 137 months; P < 0.03) (5, 6, 7, 8).…”
Section: Discussionmentioning
confidence: 99%
“…The most important consequence would be to not recognize a patient as being CRPC rather than suboptimally castrated. Based on IA testosterone level determination, prostate-specific antigen (PSA) levels and metastatic status, it is now recommended to either change the ADT drug, or add bicalutamide, enzalutamide or abiraterone acetate (Canadian guidelines) (10, 24). Herein, we propose an updated clinical decision algorithm based on the one by Klotz et al .…”
Section: Discussionmentioning
confidence: 99%
“…In some instances, it has been reported that higher degree of testosterone somehow might be the causative agent in prostate malignancy, though the exact mechanism was speculative [40]. From our previous experiment, we reported that in the presence of testosterone (male androgen hormone), aggregation of platelets was higher compared with control, whereas only ADP-induced platelet aggregation is a normal phenomenon [41]; so, prostate cancer patients are prone to AIHD in such cases.…”
Section: Discussionmentioning
confidence: 99%